The seasonal patterns of hydrographic and biogeochemical variables in the Ross Sea: A BGC-Argo analysis - Ruobing Cao; Walker O. Smith; Yisen Zhong; Stephen Riser; Kenneth S. Johnson; Lynne Talley (Deep Sea Research Part II: Topical Studies in Oceanography, 2025)

The Southern Ocean carbon and climate observations and modeling (SOCCOM) project: A review - Jorge L. Sarmiento; Kenneth S. Johnson; Lionel A. Arteaga; Seth M. Bushinsky; Heidi M. Cullen; Alison R. Gray; Roberta M. Hotinski; Tanya L. Maurer; Matthew R. Mazloff; Stephen C. Riser; Joellen L. Russell; Oscar M. Schofield; et al. (Progress in Oceanography, 2023)

Argo Data 1999–2019: Two Million Temperature-Salinity Profiles and Subsurface Velocity Observations From a Global Array of Profiling Floats - Annie P. S. Wong; Susan E. Wijffels; Stephen C. Riser; Sylvie Pouliquen; Shigeki Hosoda; Dean Roemmich; John Gilson; Gregory C. Johnson; Kim Martini; David J. Murphy; Megan Scanderbeg; T. V. S. Udaya Bhaskar; et al. (Frontiers in Marine Science, 2020)

A BGC-Argo Guide: Planning, Deployment, Data Handling and Usage - Henry C. Bittig; Tanya L. Maurer; Joshua N. Plant; Catherine Schmechtig; Annie P. S. Wong; Hervé Claustre; Thomas W. Trull; T. V. S. Udaya Bhaskar; Emmanuel Boss; Giorgio Dall’Olmo; Emanuele Organelli; Antoine Poteau; et al. (Frontiers in Marine Science, 2019)

On the Future of Argo: A Global, Full-Depth, Multi-Disciplinary Array - Dean Roemmich; Matthew H. Alford; Hervé Claustre; Kenneth Johnson; Brian King; James Moum; Peter Oke; W. Brechner Owens; Sylvie Pouliquen; Sarah Purkey; Megan Scanderbeg; Toshio Suga; et al. (Frontiers in Marine Science, 2019)

Ocean metabolism observed with oxygen sensors on profiling floats in the South Pacific - Todd R. Martz; Kenneth S. Johnson; Stephen C. Riser (Limnology and Oceanography, 2008)
We estimated rates of production and export in the South Pacific (80°W to 180°W in a zonal band between 35°S and 50°S) using 1.5 yr of oxygen measurements from profiling floats. Export production, calculated from oxygen utilization rates below the compensation depth from December to April, was 10.7 ± 2 mmol C m −2 d −1 ( n = 36, 95% CI). The corresponding satellite net primary production was 46 ± 4 mmol C m −2 d −1 , yielding a regional e‐ratio of 0.23 ± 0.05. Averaging oxygen utilization rates resulted in a net cancellation of most water mass changes related to advection and float migration. The composite vertical profile of remineralization rates, obtained by binning 36 rate profiles, agreed with published measurements based on oxygen utilization rates in hydrographic surveys and fits the classic form of a particulate organic carbon (POC) attenuation function. However, the disagreement between oxygen‐based remineralization rates and those obtained by sediment traps suggests fundamental differences between these two methods. Using float data to constrain a one‐dimensional mixed‐layer model, the annual net community production at 45°S, 144°W was ~2.5 mol C m −2 d −1 . Spatial trends in export production coinciding with the New Zealand shelf and Subtropical Front are identified.

Monsoon effects in the Bay of Bengal inferred from profiling float‐based measurements of wind speed and rainfall - S. C. Riser; J. Nystuen; A. Rogers (Limnology and Oceanography, 2008)
Both rainfall and wind have acoustic signatures that can be discerned at depths in the ocean well below the sea surface. We examine observations of rainfall and wind speed collected at a depth of 600 m in the Bay of Bengal from a specially modified Argo profiling float. In addition to the normal Argo sensors, the float carried a passive acoustic listener sensor package that monitored the spectrum of acoustic noise along the float trajectory at intervals of a few minutes and used a set of existing algorithms to estimate the wind speed and rainfall rate from these noise spectra. A comparison of the acoustically derived wind speed and rainfall estimates with analogous satellite‐derived data (rainfall from the Tropical Rainfall Measuring Mission and QwikScat winds) showed general agreement in both cases, although the float‐based measurements were representative of conditions a few kilometers around the float, whereas the remotely sensed observations were smoothed over much larger length scales. The strong monsoon signal in the Bay of Bengal is clearly present in the float‐based wind and rainfall data. The near‐surface salinity measured by the float varied because of both rainfall events and the proximity to strong coastal runoff from major rivers. The float profiles of temperature and salinity in the upper ocean, and the effects of wind and rainfall, were simulated in a version of the Price‐Weller‐Pinkel mixed‐layer model, which showed that the direct effects of most rainfall events are concentrated in the upper 20‐30 m of the water column.

Observations of pigment and particle distributions in the western North Atlantic from an autonomous float and ocean color satellite - E. Boss; D. Swift; L. Taylor; P. Brickley; R. Zaneveld; S. Riser; M. J. Perry; P. G. Strutton (Limnology and Oceanography, 2008)
Profiling floats with optical sensors can provide important complementary data to satellite ocean color determinations by providing information about the vertical structure of ocean waters, as well as surface waters obscured by clouds. Here we demonstrate this ability by pairing satellite ocean color data with records from a profiling float that obtained continuous, high‐quality optical data for 3 yr in the North Atlantic Ocean. Good agreement was found between satellite and float data, and the relationship between satellite chlorophyll and floatderived particulate backscattering was consistent with previously published data. Upper ocean biogeochemical dynamics were evidenced in float measurements, which displayed strong seasonal patterns associated with phytoplankton blooms, and depth and seasonal patterns associated with an increase in pigmentation per particle at low light. Surface optical variables had shorter decorrelation timescales than did physical variables (unlike at low latitudes), suggesting that biogeochemical rather than physical processes controlled much of the observed variability. After 2.25 yr in the subpolar North Atlantic between Newfoundland and Greenland, the float crossed the North Atlantic Current to warmer waters, where it sampled an unusual eddy for 3 months. This anticyclonic feature contained elevated particulate material from surface to 1000‐m depth and was the only such event in the float's record. This eddy was associated with weakly elevated surface pigment and backscattering, but depthintegrated backscattering was similar to that previously observed during spring blooms. Such seldom‐observed eddies, if frequent, are likely to make an important contribution to the delivery of particles to depth.